1991
DOI: 10.1128/aem.57.2.492-498.1991
|View full text |Cite
|
Sign up to set email alerts
|

Organization and nucleotide sequences of two lactococcal bacteriocin operons

Abstract: Two distinct regions of the Lactococcus lactis subsp. cremoris 9B4 plasmid p9B4-6, each of which specified bacteriocin production as well as immunity, have been sequenced and analyzed by deletion and frameshift mutation analyses. On a 1.8-kb ScaI-ClaI fragment specifying low antagonistic activity, three open reading frames (ORFs) were present, which were organized in an operon. The first two ORFs, containing 69 and 77 codons, respectively, were involved in bacteriocin activity, whereas the third ORF, containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(120 citation statements)
references
References 24 publications
5
112
0
Order By: Relevance
“…However, investigation of conjugal transfer systems in lactococci revealed that the Bac + and Imm + determinants were commonly encoded by self-transmissible elements [33,49,50]. Genetic characterization of conjugal 'Bac' determinants on pNP2 (133 kb; [51]) and p9B4-6 (60 kb; [33]) identified three distinct bacteriocins, designated lactococcins A, B, and M [21,[51][52][53][54][55]. Genetic analyses of the bacteriocin operons, coupled with biochemical analysis of lactococcin A and its mechanism of action, have uncovered an exciting model system for study of the expression, regulation, processing, and action of lactococcins [39].…”
Section: Lactococcinsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, investigation of conjugal transfer systems in lactococci revealed that the Bac + and Imm + determinants were commonly encoded by self-transmissible elements [33,49,50]. Genetic characterization of conjugal 'Bac' determinants on pNP2 (133 kb; [51]) and p9B4-6 (60 kb; [33]) identified three distinct bacteriocins, designated lactococcins A, B, and M [21,[51][52][53][54][55]. Genetic analyses of the bacteriocin operons, coupled with biochemical analysis of lactococcin A and its mechanism of action, have uncovered an exciting model system for study of the expression, regulation, processing, and action of lactococcins [39].…”
Section: Lactococcinsmentioning
confidence: 99%
“…Two bacteriocins were identified because each Imm + did not cross-protect against the other bacteriocin. DNA sequence analysis [21] revealed two distinct bacteriocin operons ( Fig. 1).…”
Section: Lactococcinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard it is notable that a group of small heat stable peptides has been defined. This includes bacteriocins produced by diverse lactic acid bacteria and sequence analysis is available for lactocins A, B and M from L. lactis [10,[121][122][123] lactocin F from Lactobacillus acidophilus [11,124], leucocin A UAL-187 from Leuconostoc gelidium [125] and pediocin PA-1 from Pediococcus acidilactici [9].…”
Section: Antimicrobialsmentioning
confidence: 99%
“…One significant trend since the last symposium is the application of protein engineering techniques in lactic acid bacteria, notable examples being the lactococcal proteinase [4], the lactose repressor gene of Lactococcus lactis [5] and the lantibiotic nisin [6,7]. Bacteriocins in general have been characterized in considerable detail, including examples of additional lantibiotics such as lactocin S from Lactobacillus sake [8] and the emergence of a group of related 'small heat stable bacteriocins' which are produced by several different species of lactic acid bacteria [9][10][11]. Interest in bacteriocins is to some extent fuelled by their potcntial as novcl biopreservativcs and several show promise in this regard.…”
Section: Introductionmentioning
confidence: 99%